Beyond Economics: Education and Culture as Key Drivers of Community Participation in Halal Tourism - Mardi, Moh.; Chandrasekar, Uma (LPPPM STAI Darul Hikmah Bangkalan, 2025)
This study aims to identify the key determinants influencing community participation in halal tourism development in Puncak Koto Panjang, Pasaman Regency, Indonesia. Given the increasing prominence of halal tourism, understanding socio-economic and cultural factors affecting local engagement is crucial for sustainable development. A quantitative approach was employed, utilizing multiple linear regression analysis in SPSS 25. Data were collected from 383 respondents, consisting of key stakeholders in the tourism sector. The research assessed five independent variables: economic factors, leadership, motivation, education, and socio-cultural aspects. The results indicate that economic (t = 1.830, p < 0.05), education (t = 5.998, p < 0.05), and socio-cultural factors (t = 5.303, p < 0.05) significantly influence the development of halal tourism. However, leadership and motivation factors were found to be statistically insignificant. These findings suggest that financial stability, educational awareness, and cultural preservation play a vital role in fostering sustainable halal tourism. This study provides empirical evidence for policymakers and tourism stakeholders to formulate effective strategies. Encouraging economic growth, enhancing community education, and integrating cultural heritage into tourism initiatives can boost community participation. This research contributes to the existing literature by providing an empirical analysis of community engagement in halal tourism, particularly in an emerging market context. The findings emphasize the significance of socio-economic and cultural dimensions in sustaining halal tourism destinations.